Human IgG lacking effector functions demonstrate lower FcRn-binding and reduced transplacental transport. (March 2018) - Stapleton, Nigel M.; Armstrong-Fisher, Sylvia S.; Andersen, Jan Terje; van der Schoot, C. Ellen; Porter, Charlene; Page, Kenneth R.; Falconer, Donald; de Haas, Masja; Williamson, Lorna M.; Clark, Michael R.; Vidarsson, Gestur; Armour, Kathryn L.
Highlights: IgG1 modified to reduce cytotoxicity (G1Δnab) has impaired FcRn-mediated function. G1Δnab variants bind FcRn in a pH-dependent manner but with altered kinetics. G1Δnab variants are transported to a lesser degree across polarized cells and placenta. Data collectively point to residues originating from IgG2 affecting IgG transport. Abstract: We have previously generated human IgG1 antibodies that were engineered for reduced binding to the classical Fcγ receptors (FcγRI–III) and C1q, thereby eliminating their destructive effector functions (constant region G1Δnab). In their potential use as blocking agents, favorable binding to the neonatal Fc receptor (FcRn) is important to preserve the long half-life typical of IgG. An ability to cross the placenta, which is also mediated, at least in part, by FcRn is desirable in some indications, such as feto-maternal alloimmune disorders. Here, we show that G1Δnab mutants retain pH-dependent binding to human FcRn but that the amino acid alterations reduce the affinity of the IgG1:FcRn interaction by 2.0-fold and 1.6-fold for the two antibodies investigated. The transport of the modified G1Δnab mutants across monolayers of human cell lines expressing FcRn was approximately 75% of the wild-type, except that no difference was observed with human umbilical vein endothelial cells. G1Δnab mutation also reduced transport in an e x vivo placenta model. In conclusion, we demonstrate that, although the G1Δnab mutations are away from the FcRn-binding site, they have long-distance effects, modulating FcRn binding and transcellular transport. Our findings have implications for the design of therapeutic human IgG with tailored effector functions.